Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2015
DOI: 10.2118/176371-ms
|View full text |Cite
|
Sign up to set email alerts
|

Tiltmeter Hydraulic Fracturing Mapping on a Cluster of Horizontal Wells in a Tight Gas Reservoir

Abstract: This reservoir is a tight gas field and the target sand stone zones are generally staged fracturing treated at depths of roughly 1500 to 2800 meter. Knowing the direction or azimuth of the fracture orientation is important in development of this low permeability reservoir with horizontal wells. The paper presents surface tiltmeter hydraulic fracturing mapping results of 15 stages treatment in two horizontal wells at the same operational period. The two wells are part of a cluster of six horizontal wells locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…They reported expanded steps in the geomechanical inversion technique for determining the areal extent of the fracture network. Similarly, [81] presented a case study for a tight gas reservoir with a cluster of horizontal wells. They found that the tiltmeter could monitor the fracture network growth during synchronous fracturing across multiple wells.…”
Section: Distributed Acoustic Sensing (Das)mentioning
confidence: 99%
“…They reported expanded steps in the geomechanical inversion technique for determining the areal extent of the fracture network. Similarly, [81] presented a case study for a tight gas reservoir with a cluster of horizontal wells. They found that the tiltmeter could monitor the fracture network growth during synchronous fracturing across multiple wells.…”
Section: Distributed Acoustic Sensing (Das)mentioning
confidence: 99%
“…In particular, Warpinski (2014) described the current and future uses that tiltmeters network can provide when used in unconventional operating conditions. This includes: 1) mapping fracture's network (Wright et al, 1998;Wright et al, 1997;Zhou et al, 2015), 2) orthogonal and horizontal fractures identification, 3) refracturation processes and 4) fracture's network evolution during fracking processes. Because the ground deformation induced by a single frack is so small (tens of nanometers, Astakhov et al, 2012), only tiltmeters and strainmeters can measure it.…”
Section: Instrumental Drift and Noise Can Bementioning
confidence: 99%
“…Dvorak & Dzurizin, 1997;Masterlark, 2007). Models of magma plumbing systems often include a magma reservoir (pressure source), a conduit (cylinder or ellipsoidal sources) or a dike (planar dislocation), which may or may not reach the surface (Bato et al, 2017;Bonaccorso et al, 2008;Montgomery-Brown et al, 2010;Palano et al, 2008;Segall, 2013), while models of stimulated reservoir volume in hydraulic-fracture treatment consider the superposition of several nearby fractures assimilated to planar dislocations (Astakhov et al, 2012;Warpinski, 2014;Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kamo and Ishihara (1989) and Nishi et al (2007) detected deformation of the order of a nanorad in volcano monitoring, with a maximum precursory tilt change of 10-200 nrad for periods ranging from 10 minutes to 7 hours prior to eruptions. Hydraulic fracturing of low permeable reservoirs (Astakhov et al, 2012;Castillo et al, 1997;Zhou et al, 2015), phreatic eruption (Honda et al, 2018), long term injection of water into borehole (Jahr et al, 2006(Jahr et al, , 2008 or changes in pump rates in the vicinity of fluid-producing wells (Chen et al, 2010) produce small deformation signals detectable by tiltmeters. In addition to the source signal, tilt signal is altered by other strain sources due to tides, hydraulic loading, temperature effect or pressure gradient.…”
Section: Introductionmentioning
confidence: 99%